Review of the genus Jilinga Ghauri (Cicadellidae: Deltocephalinae: Paralimnini) in Pakistan with description of two new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
Species of the leafhopper genus Jilinga Ghauri from Pakistan are reviewed and two new species, Jilinga neelumensis sp. nov. and Jilinga truncata sp. nov. are described and illustrated with photographs. A key is given to distinguish all the species (males) of the genus from Pakistan.